1986
DOI: 10.1093/clinchem/32.11.2030
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous liquid-chromatographic determination of 3,4-dihydroxyphenylglycol, catecholamines, and 3,4-dihydroxyphenylalanine in plasma, and their responses to inhibition of monoamine oxidase.

Abstract: This is a reversed-phase liquid-chromatographic method, with electrochemical detection, for simultaneously measuring, in plasma, the concentrations of the catecholamine precursor dihydroxyphenylalanine (DOPA); the endogenous catecholamines norepinephrine, epinephrine, and dopamine; and the deaminated catecholamine metabolites dihydroxyphenylacetic acid (DOPAC) and dihydroxyphenylglycol (DHPG). We used this method to assess effects of monoamine oxidase (EC 1.4.3.4) inhibition in humans. Plasma DHPG concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
2
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(109 citation statements)
references
References 17 publications
0
105
2
2
Order By: Relevance
“…The same authors also reported on a preliminary human experiment, where 40 mg of cimoxatone, a reversible MAO-A inhibitor, reduced plasma DHPG levels by 75%, whereas plasma DHPG was unaltered after 5 days' treatment with deprenyl 10 mg daily (Brown & Monks, 1984). On the other hand, chronic treatment of elderly humans with larger doses of deprenyl (30-60 mg/day) has been reported to reduce plasma DHPG levels by 70%, a decrement comparable with that seen after treatment with tranylcypromine (75%), a non-selective MAO inhibitor (Eisenhofer et al, 1986). This may reflect loss of MAO-B selectivity for higher doses of deprenyl upon repeated administration Sunderland etal., 1987), or alternatively, a more complex relationship between the pharmacological effects of deprenyl and plasma DHPG levels (Liebowitz et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…The same authors also reported on a preliminary human experiment, where 40 mg of cimoxatone, a reversible MAO-A inhibitor, reduced plasma DHPG levels by 75%, whereas plasma DHPG was unaltered after 5 days' treatment with deprenyl 10 mg daily (Brown & Monks, 1984). On the other hand, chronic treatment of elderly humans with larger doses of deprenyl (30-60 mg/day) has been reported to reduce plasma DHPG levels by 70%, a decrement comparable with that seen after treatment with tranylcypromine (75%), a non-selective MAO inhibitor (Eisenhofer et al, 1986). This may reflect loss of MAO-B selectivity for higher doses of deprenyl upon repeated administration Sunderland etal., 1987), or alternatively, a more complex relationship between the pharmacological effects of deprenyl and plasma DHPG levels (Liebowitz et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…Measurements of plasma-free and plasma-deconjugated normetanephrine and metanephrine concentrations were performed using liquid chromatography with electrochemical detection (LC-ECD) as described elsewhere. 20 For determination of plasma-deconjugated metanephrines 200-ll samples of plasma were incubated for 30 min at 37°C with 0Á5 units of sulphatase (Sigma, St. Louis, MO, USA). Samples of enzyme-processed plasma for measurements of deconjugated metanephrines were then subjected to the same solid-phase extraction and LC-ECD procedures as samples of plasma-free metanephrines.…”
Section: Analyses Of Metanephrinesmentioning
confidence: 99%
“…NE, E, M and NM were determined by high pressure liquid chromatography with electrochemical detection (HPLC-ED). 25,26 VMA was assayed by a spectrophotometric method. 27…”
Section: Catecholamine Studiesmentioning
confidence: 99%